PENGARUH RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Safaruddin; Sitti Anugrah; La Ode Anto (Accounting Student Series on Emerging Trends, 2026)
This study examines the effect of Return on Assets and Debt to Equity Ratio on Tax Avoidance in coal mining sub sector companies listed on the Indonesia Stock Exchange from 2019 to 2024. ROA is used as a proxy for profitability, while DER represents leverage. Tax Avoidance is measured using the Effective Tax Rate (ETR). The study employs a quantitative approach using secondary data obtained from companies’ annual financial statements. Purposive sampling was applied, resulting in a sample of 21 companies. Panel data regression analysis was conducted using EViews 13 software. The results indicate that Return on Assets has a significant effect on Tax Avoidance, and Debt to Equity Ratio also significantly affects Tax Avoidance. Additionally, Return on Assets and Debt to Equity Ratio simultaneously have a significant influence on Tax Avoidance. These findings suggest that company profitability and capital structure play a crucial role in influencing tax avoidance practices through tax planning strategies that remain compliant with applicable tax regulations.